2008
DOI: 10.1111/j.1600-0668.2007.00513.x
|View full text |Cite
|
Sign up to set email alerts
|

Microbial volatile organic compounds in the air of moldy and mold-free indoor environments

Abstract: The assumption that mold infestations might be detected by microbial VOC emissions must be considered with great reservation. The major part of the total variability of the measured MVOC concentrations originates from not known influencing factors and/or from factors not directly associated with the mold status of the dwellings (confounders). More specific and sensitive markers for the assessment of the mold status should be found, if the screening for mold infestations should be performed by volatile organic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(49 citation statements)
references
References 42 publications
(45 reference statements)
0
46
0
2
Order By: Relevance
“…In the previous study, 1-octen-3-ol associated with inspected mold status; however, in only a small portion (Schleibinger et al, 2008) and there must be other sources such as hidden mold growth due to condensation on walls (Small, 2003).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In the previous study, 1-octen-3-ol associated with inspected mold status; however, in only a small portion (Schleibinger et al, 2008) and there must be other sources such as hidden mold growth due to condensation on walls (Small, 2003).…”
Section: Discussionmentioning
confidence: 76%
“…However, compounds, so-called MVOC, are also emitted from plants, furniture, furnishing, and building materials (Konig et al, 1995;Korpi et al, 1999;Pasanen et al, 1998;Schleibinger et al, 2004). Previous studies failed to find any strong association between indoor mold status and MVOC (Schleibinger et al, 2005;Schleibinger et al, 2008).…”
Section: Introductionmentioning
confidence: 71%
“…The exact concentration of any given fungal VOC in water-damaged, moldy buildings is difficult to measure because concentrations vary depending on the ventilation rate, moisture, temperature, and other parameters. However, reported concentrations of 1-octen-3-ol in moldy buildings and classrooms range from 0.2 μg/m 3 (0.00004 ppm) up to 900 μg/m 3 (0.16 ppm) (15,(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…Many published studies have confirmed the presence of fungal contamination in indoor environments and it has been reported that fungal spores and microbial volatile organic compounds (MVOCs) emitted from fungi have adverse health effects [1][2][3][4][5][6][7][8]. Fungal growth in indoor environments is strongly related to the indoor physical and chemical conditions, such as atmospheric air temperature, relative humidity, hydrogen-ion exponent (pH) in free water and nutrients; therefore, a comprehensive prediction method must be developed to estimate fungal growth and the subsequent health risk of fungal contamination for exposed individuals.…”
Section: Introductionmentioning
confidence: 99%